Causal Associations of Epigenetic Age Acceleration With Stroke and Its Functional Outcome: A Two‐Sample, Two‐Step Mendelian Randomization Study - Baizhi Qiu; Shuyang Wen; Zifan Li; Yuxin Cai; Qi Zhang; Yuting Zeng; Shuqi Zheng; Zhishan Lin; Yupeng Xiao; Jihua Zou; Guozhi Huang; Qing Zeng (Brain and Behavior)
ABSTRACT Background Emerging evidence from observational studies suggested that epigenetic age acceleration may result in an increased incidence of stroke and poorer functional outcomes after a stroke. However, the causality of these associations remains controversial and may be confounded by bias. We aimed to investigate the causal effects of epigenetic age on stroke and its functional outcomes. Methods We conducted a two‐sample Mendelian randomization (MR) analysis to explore the causal relationships between epigenetic age and stroke and its outcomes. Additionally, a two‐step MR analysis was performed to investigate whether lifestyle factors affect stroke via epigenetic age. Datasets of epigenetic age were obtained from a recent meta‐analysis (n = 34,710), while those of stroke and its outcomes were sourced from the MEGASTROKE (n = 520,000) consortium and Genetics of Ischaemic Stroke Functional Outcome (GISCOME) network (n = 6165). Results Two‐sample MR analysis revealed a causal relationship between PhenoAge and small vessel stroke (SVS) (OR = 1.07; 95% CI, 1.03–1.12; p = 2.01 × 10−3). Mediation analysis through two‐step MR indicated that the increased risk of SVS due to smoking initiation was partially mediated by PhenoAge, with a mediation proportion of 9.5% (95% CI, 1.6%–20.6%). No causal relationships were identified between epigenetic age and stroke outcomes. Conclusions Our study supports using epigenetic age as a biomarker to predict stroke occurrence. Interventions specifically aimed at decelerating epigenetic aging, such as specific lifestyle changes, offer effective strategies for reducing stroke risk.